2019
DOI: 10.3390/s19112536
|View full text |Cite
|
Sign up to set email alerts
|

Joint Resource Optimization in Simultaneous Wireless Information and Power Transfer (SWIPT) Enabled Multi-Relay Internet of Things (IoT) System

Abstract: The internet of things (IoT) is becoming more indispensable in modern society as the further development and maturity of information technology progresses. However the exponential growth of IoT devices leads to severe energy consumption. As a technology with broad application prospects, simultaneous wireless information and power transfer (SWIPT) enables IoT devices to harvest energy from receiving radio frequency (RF) signals while ensuring information transmission. In this paper, we investigate the transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Given this, the conventional works, such as [9,11,25,33,34], usually convert the received signal y EH i (t) into the DC power with a linear function. However, a nonlinear function for the energy conversion would be more practical, and the previous works, such as [30,31], adopted the logarithmic nonliner EH model for the ith IoT device on the jth sub-carrier as follows:…”
Section: Network and Channel Modelsmentioning
confidence: 99%
“…Given this, the conventional works, such as [9,11,25,33,34], usually convert the received signal y EH i (t) into the DC power with a linear function. However, a nonlinear function for the energy conversion would be more practical, and the previous works, such as [30,31], adopted the logarithmic nonliner EH model for the ith IoT device on the jth sub-carrier as follows:…”
Section: Network and Channel Modelsmentioning
confidence: 99%
“…Results showed that CoR with diversity increases the data rates for individual IoT devices while enhancing the sum rate of overall network. Lu et al devised an optimization problem for transmission rate maximization in a multi-relays Orthogonal Frequency Division Multiplexing (OFDM) based IoT network [146]. Simulation results based on effect of number of relays, conversion efficiency and power splitting ratio on transmission rate proved that the rate of transmission is increased considerably by the suggested scheme.…”
Section: Swipt Cor For Internet Of Things (Iot)mentioning
confidence: 99%
“…Power switching has been considered for IoT networks with SWIPT relays [48], [49] and [50]. D. Asiedu et al [48] proposed a PS ratio for SWIPT relays without external energy sources in a downlink multihop IoT PS ratio optimization [50] PS ratio optimization SWIPT(TS) [51] Power and subcarrier allocation [52] TS ratio and relay power optimization [53] Transmission time optimization [4] Outage probability minimization [54] Sum-rate maximization [55] Outage probability and Ergodic probability analysis SWIPT [56] Error (Dual PS and TS) probability analysis [57] Outage probability analysis [58] Outage probability analysis Green energy [59] Distortion harvesting reduction maximization [43] Bandwidth and power optimization Shorter frame length for information decoding [56] information transmission [56] network using DF protocols at the relays. Source transmit power minimization and system throughput maximization problems were formulated subject to energy and power ratio constraints.…”
Section: ) Power Splitting In Swipt Relay-enabled Iotmentioning
confidence: 99%